DESIGNING A WEB-BASED ACTIVITY MANAGEMENT SYSTEM FOR ENHANCED DATA ANALYTICS PERFORMANCE - Hartatik Hartatik; Fitria Alfiana; Suci Wulandari (Yayasan Education and Social Center, 2023)
Recording activities in an organization or institution is very important so that activities can run well, as well as recording activities related to worship activities. This research is motivated by problems in team, the study of mosques in Central Java, which currently does not have an information system in managing mosque activities and implementation data analitycs for enhanced performance activity. The large number of activities in the place of worship and all activities have not been properly recorded and manual data processing makes it difficult for mosque administrators to process data and takes a long time. To overcome this problem, a management system is needed that can be easily accessed by mosque administrators and provides precise and accurate information about activities to the community. The research conducted in this final project is to create and design a web-based information system for mosques. Which information system is made with Hypertext Preprocessor (PHP), CodeIgniter Framework and MySQL database. The research method used is waterfall. Starting with system analysis, design, coding and the final stage is system testing. The purpose of the system design that will be made is to make it easier for mosque administrators to manage data on mosque activities and make it easier for the public to find information. And for users in submitting donations or activities, they don't need to come directly to the mosque because they can apply through the system